Blurring the Human-Animal Dichotomy: A Deep Ecological Reading of Indra Sinha’s Animal’s People - Sharma, Kamal (The Outlook: Journal of English Studies, 2022)
The paper analyzes human-animal relation in Indra Sinha’s Animal’s People (2007) from the deep ecological perspective. The narrator of the story, a teenager, who prefers to be called ‘Animal,’ recounts his experiences of physical deformity and friendship with his friend Lara – a dog. By praising animal (dog) and criticizing human world, the character Animal blurs the dichotomy between human and non-human world by realizing the intrinsic value of each life form. Animal’s act of calling himself ‘Animal’ rather than human shows his disgust to humanity as he has been a victim of industrial disaster – Bhopal gas tragedy as an outcome of modern development of humanity. His infatuation to animals, open sky and forests shows his love to non-human world as he sees intrinsic values of each thing. It supports what the deep ecologists call it as having intrinsic values of biotic and abiotic things in themselves irrespective of what humans define it for utilitarian purpose. The study is qualitative in nature and analyzes the text from the deep ecological perspective. The paper concludes that by blurring the human-animal dichotomy, the narrator enjoys his emotional relation with animal (dog) and nature.